Cultura na escola: produção de material didático a partir da análise do consumo cultural entre estudantes do ensino médio - Freitas, Tarsizio Cipriano (2023)
This paper is about the presentation of didactic material produced with the theme of cultural consumption by high school students. To accomplish this task, it was sought, at first, to capture the initial sense that high school students have about culture through questionnaires applied online ( by Google Forms) in order to capture general issues about culture and cultural consumption of this public. Following the research, weworked, according to the sociological perspective, the key concepts of culture developed by Félix Guattari and Suely Rolnik, which involve the theme addressed and,finally, at the conclusion, we produced didactic material in the format of a cultural guidebook. Together with the cultural guidebook, it was proposed to the students to produce audiovisual material in the format of mini-documentaries, in which there would be a theoretical deepening of what was worked in the classroom through the guidebook. The results were presented through the answers to the follow-up instruments developed during the classes, the elaboration and exhibition of the mini-documentaries, the final production of the cultural guidebook and, finally, the perception that the young people researched had about the cultural universe through the discussion on the theme of culture and cultural consumption in the classroom. As a conclusion, we sought to share information, knowledge, and strategies to expand the horizons and cultural possibilities.